Об этнографическом измерении материальности - Baranov, Dmitriy Aleksandrovich (Studia Slavica et Balcanica Petropolitana, 2018)
The article discusses the ethnographic approaches to the study of material culture and the place they have taken within the material turn that has occurred in the social sciences in recent decades. Despite the fact that at the stage of its formation, ethnography was understood primarily as a study of the material culture of different nations, however, the material nature of the thing turned out to be poorly problematized. Until now, the conservative line dominates the ethnographic approach to material culture, within which the focus is either «material» (material, manufacturing techniques, utilitarian functions) or «symbolic» (semantics, ritual functions). The object-centric perspective proposed by sociologists, equalizing subject and object, the human being and thing, is hardly fully in the interests of ethnography. For the latter, promising approaches to material study are largely determined by the consideration of its physical features that appeal to human feelings. It is in this «contact zone» of human interaction with a thing — the sphere of human feelings that a thing acquires a human dimension, which, in fact, is the subject field of anthropology / ethnography.